Studies in law, politics and society. Vol. 53 - Sarat, Austin (Emerald, 2010)
This volume of Studies in Law, Politics, and Society includes a special collection of chapters entitled 'Making Sense of the Past: When History Meets Law.' The articles in this symposium consider the ways in which history has shaped law and how we make sense of past events. In addition, the volume contains general articles that explore pressing legal issues such as the prison boom, First Amendment controversies, and the work of cause lawyers. As has long been the tradition with this series, Volume 53 illustrates the vibrancy of interdisciplinary legal scholarship throughout.
Keywords: Law -- Government -- General.; Law -- General.; Law -- Legal History.; Law & society.; Legal system: general.; Sociological jurisprudence.; Law -- Political aspects.; elektronické knihy; electronic books